Generation of Jewish Apocalyptics: Problems of the Genre Definition and Origins - Svetlana Kareva (Вестник Свято-Филаретовского института, 2014)
This article is devoted to the study of Jewish apocalyptics as a literary genre. The article provides an overview of scholars’ viewpoints on research questions associated with the definition of apocalypse genre, its origins and determining factors of development. The article considers theories of generating apocalyptics from the Old Testament prophecies, including those associating the apocalyptic tradition with visionary dreams of the prophets, where there are presented mythological motifs of universe creation and cosmic battles borrowed from other cultures of the Middle East.